Perfil emocional de un grupo de militares colombianos víctimas de minas antipersona o artefactos explosivos improvisados (2014)
Introduction Antipersonnel Mines (MAP) and Improvised Explosive Devices (IEDs) are frequently used in Colombia as an armed resource without the need for direct combat. The Department of Antioquia has the highest number of events associated with the detonation of such battle techniques. There are no studies on the psychological effects that appear as a result of accidents with Antipersonnel Mines and IEDs in the military population. Objective To establish the psychological profile of a group of military victims of MAP and AEI, and a control group of soldiers who were not victims from the analysis of four emotional variables (depression, anxiety, anger and stress). Methods The research was conducted using a case-control design in a.quantitative, comparative, descriptive and cross-sectional study. Participants: A sample of 80 soldiers assigned to the Seventh Division of the National Army of Colombia at Medellin, Antioquia. The sample included a group of 30 military cases and 50 soldiers as controls. Results The anxiety state, trait anxiety, state anger, and trait anger variables showed statistically significant differences between groups. There were no significant differences in the variables depression and stress between groups variables. There was no depression, anxiety, or stress in either of the two groups, but there were clinically significant levels of anger in both groups. © 2013 Asociación Colombiana de Psiquiatría. Published by Elsevier España, S.L. All rights reserved.